2013
DOI: 10.1016/j.ajhg.2013.09.008
|View full text |Cite
|
Sign up to set email alerts
|

ERBB4 Mutations that Disrupt the Neuregulin-ErbB4 Pathway Cause Amyotrophic Lateral Sclerosis Type 19

Abstract: Amyotrophic lateral sclerosis (ALS) is a devastating neurological disorder characterized by the degeneration of motor neurons and typically results in death within 3-5 years from onset. Familial ALS (FALS) comprises 5%-10% of ALS cases, and the identification of genes associated with FALS is indispensable to elucidating the molecular pathogenesis. We identified a Japanese family affected by late-onset, autosomal-dominant ALS in which mutations in genes known to be associated with FALS were excluded. A whole-ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(87 citation statements)
references
References 22 publications
2
82
0
Order By: Relevance
“…This finding is in agreement with previous reports of loss-of-function ErbB4 mutations as causative of late-onset ALS (Takahashi et al, 2013).…”
Section: Panel)supporting
confidence: 83%
See 2 more Smart Citations
“…This finding is in agreement with previous reports of loss-of-function ErbB4 mutations as causative of late-onset ALS (Takahashi et al, 2013).…”
Section: Panel)supporting
confidence: 83%
“…It was recently reported that loss-of-function mutations on the Nrg1 receptor ErbB4 produce a form of late-onset, autosomal-dominant ALS in humans (Takahashi et al, 2013), opening a new field for searching novel therapeutic approaches. Thereby, the main goal of the present work was to determine the role of soluble Nrg1-I in ALS by assessing the effect of its overexpression at the NMJs in SOD1 G93A mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ALS19 (MIM #615515) represents a rare autosomal dominant form of late-onset slowly progressive familial ALS described in japanese and canadian families, resulting from heterozygous missense mutations in ERBB4 gene (V-ERB-B2 avian erythroblastic leucemia viral oncogene homolog 4; 2q34), coding the HER4 protein ligand for NDF/heregulin and neurregulin-ERBB4 pathways, involved in synaptic plasticity, cell proliferation and differentiation, glutamatergic hypofunction, and inhibition of NMDA currents and raise of AMPA currents 40 .…”
Section: Als19mentioning
confidence: 99%
“…ERBB4 point mutations were introduced into pcDNA3.1.ERBB4JM-aCYT-2-HA and pBABE-puroERBB4JM-aCYT-2-HA by site-directed mutagenesis as previously described. 37 The pcDNA3.1.ERBB2 (ref. 13) construct was used to transiently overexpress ERBB2.…”
Section: Expression Plasmidsmentioning
confidence: 99%